The Impact of Gender Stereotypes on the Mental Health and Well-Being of Transgender and Non-Binary Individuals in Bangladesh - Dheeraj, Chudar (International Journal of Gender Studies, 2024)
Purpose: The aim of the study was to investigate the impact of gender stereotypes on the mental health and well-being of transgender and non-binary individuals. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Gender stereotypes negatively impact the mental health of transgender and non-binary individuals, leading to heightened levels of stress, anxiety, and depression. Discrimination and marginalization exacerbate feelings of social isolation and low self-esteem among this population. Internalization of negative stereotypes further worsens mental health issues and hinders access to necessary support services. Addressing gender stereotypes is crucial for promoting the well-being of transgender and non-binary individuals and creating inclusive environments that validate their identities. Unique Contribution to Theory, Practice and Policy: Minority stress theory, social identity theory, intersectionality theory may be used to anchor future studies on the impact of gender stereotypes on the mental health and well-being of transgender and non-binary individuals. Apply machine learning and dimension reduction techniques to genomic data to advance the field of precision medicine. Formulate policies and regulations that address privacy and ethical concerns when dealing with sensitive data, such as genomic information and personal text data